The effects of companies’ social irresponsibility on consumers’ negative emotions toward the brand and their behavior - Nasab, Seyyed Mohammad Tabataba'i; Abikari, Masoome (UI Scholars Hub, 2021)
Consumers’ negative emotions may be the main cause of behaviors such as complaining, negative word of mouth, and brand switching. In this regard, factors other than brand can produce negative or positive emotions toward a brand. One such factor is corporate social irresponsibility (CSIR). This study seeks to extract negative emotions toward a particular brand (auto brand). The results show that consumers’ negative emotions toward the auto brand are mainly characterized by anxiety, discontent, and anger. Also, the study model indicates a significant positive correlation between consumers’ negative emotions and their behavioral approaches (e.g., complaining, negative word of mouth, brand switching). On the other hand, the model represents the mediating role of negative word of mouth in brand switching. Finally, this study investigates the moderating role of CSIR and shows that it can increase the possibility of brand switching in consumers up to 40%.